2012
DOI: 10.1007/978-3-7091-0956-4_60
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiography as a Confirmatory Test in Brain Death

Abstract: CT angiography is a promising method of evaluating intracranial circulatory arrest in brain death with a high spatial and temporal resolution, superior to all other established technical procedures. The examination is easily accessible in most hospitals, operator independent, minimally invasive and inexpensive. Therefore, CT angiography has the potential to enlarge the existing armamentarium of confirmatory brain death tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…The only remnant flow that was observed in a minority of patients was the filling of a short segment of the proximal intradural VA (proximal V4), which does not exclude BD. This finding is similar to intracranial non-filling observed in some other studies [ 2 , 5 - 6 , 19 ] and simulates the characteristic findings observed in conventional angiography [ 2 , 9 ]. This finding may yield to 100% specificity for the diagnosis of BD.…”
Section: Discussionsupporting
confidence: 92%
“…The only remnant flow that was observed in a minority of patients was the filling of a short segment of the proximal intradural VA (proximal V4), which does not exclude BD. This finding is similar to intracranial non-filling observed in some other studies [ 2 , 5 - 6 , 19 ] and simulates the characteristic findings observed in conventional angiography [ 2 , 9 ]. This finding may yield to 100% specificity for the diagnosis of BD.…”
Section: Discussionsupporting
confidence: 92%
“…The preliminary results of this study were presented on the 14th International Conference on Intracranial Pressure and Brain Monitoring (September 2010, Tuebingen, Germany) [12]. The preliminary results of this study were presented on the 14th International Conference on Intracranial Pressure and Brain Monitoring (September 2010, Tuebingen, Germany) [12].…”
Section: Introductionmentioning
confidence: 99%
“…We present our results on intracranial contrast enhancement in arterial and venous scanning series of cranial vascular territories in BD, compared to the well-established tests like electroencephalography (EEG) and Transcranial Doppler Ultrasonography (TCD) and propose a protocol to determine intracranial circulatory arrest in BD with CT-A, evaluating anterior as well as posterior circulation. The preliminary results of this study were presented on the 14th International Conference on Intracranial Pressure and Brain Monitoring (September 2010, Tuebingen, Germany) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have attempted to show the reliability of CTA in demonstrating a lack of intracranial blood flow in the brain-dead patient. [1][2][3][5][6][7][8][9][10][12][13][14][15][17][18][19] However, these studies are highly heterogeneous in terms of the comparison studies they use as gold standards; some appropriately use clinical criteria alone, whereas others use a combination of clinical criteria and any one or a combination of the AAN-recommended ancillary tests. The use of ancillary tests other than CA as gold standards to compare with CTA is problematic, as many of these studies have a statistical performance similar to that of CTA.…”
mentioning
confidence: 99%